Effectiveness of Social Media in Culinary and Tourism Marketing (Jurnal Destinasi Pariwisata, 2025)
This meta-analysis examines the impact of social media on culinary and tourism marketing, synthesizing previous studies. Results show that the use of social media significantly increases marketing effectiveness, engagement and tourist visits to culinary and tourism destinations. Culinary destinations and businesses that use social media have higher visitation rates than those that do not. A lower bound value of -0.045 and an upper bound of 1.247 with an average effect size of 0.61 indicate a strong impact. Variation in marketing effectiveness is evidenced by a Q value of 2449.890; p < .001. This research provides a strong basis for marketing practitioners in the tourism and culinary industries to better understand and utilize social media in their marketing strategies, in order to achieve better marketing objectives and improve the reputation of destinations and culinary businesses.
Keywords: Social Media; Culinary; Tourism